Kontribusi Budaya Organisasi, Etos Kerja dan Komunikasi Interpersonal Kepala Sekolah Terhadap Motivasi Kerja Guru di SMA Jembatan Budaya - N.N.A. Erawati; I.P.W Ariawan; D.G.H Divayana (Pascasarjana Universitas Pendidikan Ganesha, 2021)
The researcher hopes that this research will be able to find out the contribution of organizational culture, work ethic and principal's interpersonal communication to the work motivation of teachers at Jembatan Budaya High School. The researcher used an